1988
DOI: 10.1099/00221287-134-9-2599
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Monoclonal Antibodies Specific for Mycobacterium bovis

Abstract: A series of monoclonal antibodies (MAbs), specific for Mycobacterium bovis and BCG strains, were tested extensively for cross-reactivity to a wide range of mycobacterial species using ELISA, Western blotting and dot-blot analysis. The MAbs bound specifically to M . bovis and BCG and showed limited cross-reactivity with some strains of M . tuberculosis. All these MAbs recognized a 22 kDa protein previously termed MPB70, and by competitive ELISA analysis appeared to detect at least three M . bovis-specific deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 15 publications
1
26
0
3
Order By: Relevance
“…1) A second area, containing epitopes for SB5,6, 7 and 8 was mapped towards the carboxyl terminal of the molecule. Competition analysis of 10 SB MoAb showed that they could be grouped into three sets (23). SB5, 6, 7 and 8 competed with each other indicating that they bound to the same or neighbouring epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1) A second area, containing epitopes for SB5,6, 7 and 8 was mapped towards the carboxyl terminal of the molecule. Competition analysis of 10 SB MoAb showed that they could be grouped into three sets (23). SB5, 6, 7 and 8 competed with each other indicating that they bound to the same or neighbouring epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant GST fusion antigens were tested in an EIA for reactivity with nine MoAb which recognize at least three separate epitopes on MPB70 (Table 3) (23). The controls were the same as in the T cell assays.…”
Section: Analysis Of B Cell Epitopes By Eiamentioning
confidence: 99%
See 2 more Smart Citations
“…and TB1 R (5?-AGC ACG CTG TCA ATC ATG TA-3?) amplify a 372-bp region of the gene responsible for the production of MPB 70, a secretory protein considered to be specific for M. tuberculosis complex (Wood et al 1988;Cousins et al 1991).…”
Section: Laboratory Proceduresmentioning
confidence: 99%